Etiology of urethral discharge in West Africa: the role of Mycoplasma genitalium and Trichomonas vaginalis - Pépin Jacques; Sobéla François; Deslandes Sylvie; Alary Michel; Wegner Karsten; Khonde Nzambi; Kintin Frédéric; Kamuragiye Aloys; Sylla Mohammed; Zerbo Petit-Jean; Baganizi Énias; Koné Alassane; et al. (The World Health Organization, 2001)
OBJECTIVE: To determine the etiological role of pathogens other than Neisseria gonorrhoeae and Chlamydia trachomatis in urethral discharge in West African men. METHODS: Urethral swabs were obtained from 659 male patients presenting with urethral discharge in 72 primary health care facilities in seven West African countries, and in 339 controls presenting for complaints unrelated to the genitourinary tract. Polymerase chain reaction analysis was used to detect the presence of N. gonorrhoeae, C. trachomatis, Trichomonas vaginalis, Mycoplasma genitalium, and Ureaplasma urealyticum. FINDINGS: N. gonorrhoeae, T. vaginalis, C. trachomatis, and M. genitalium - but not U. urealyticum - were found more frequently in men with urethral discharge than in asymptomatic controls, being present in 61.9%, 13.8%, 13.4% and 10.0%, respectively, of cases of urethral discharge. Multiple infections were common. Among patients with gonococcal infection, T. vaginalis was as frequent a coinfection as C. trachomatis. M. genitalium, T. vaginalis, and C. trachomatis caused a similar clinical syndrome to that associated with gonococcal infection, but with a less severe urethral discharge. CONCLUSION: M. genitalium and T. vaginalis are important etiological agents of urethral discharge in West Africa. The frequent occurrence of multiple infections with any combination of four pathogens strongly supports the syndromic approach. The optimal use of metronidazole in flowcharts for the syndromic management of urethral discharge needs to be explored in therapeutic trials.